Repression in the University of Zaragoza: the Role of the Court of Public Order - Calvo Romero, Sergio (CIAN-Revista de Historia de las Universidades, 2016)
The 1960s began a new type of University protest in which the protagonists, the objectives and the confrontational actions constituted novelty that the regime failed to recognize and whose physical and judicial repression solution. The University of Zaragoza became a continuous focus of challenge to the regime. The legal tool that was used was the jurisdiction of public order and the public order Court. Analysis of judgments constitutes a primary source of extraordinary importance which reveals to us that the students of Zaragoza were active and crucial part of the anti-Franco struggle in the capital. The campus was the protagonist of demonstrations, assemblies and other signs of unrest, highlighting the Communist Party of Spain in their effort to lead and promote the student protests.
Keywords: Tribunal of public order; student protests; University of Zaragoza; youth; repression; detention